2012
DOI: 10.4088/jcp.11m07031
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Add-On Randomized Controlled Trial of Low-Dosed-Serine for Negative and Cognitive Symptoms of Schizophrenia

Abstract: ClinicalTrials.gov identifier: NCT00138775.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 0 publications
0
62
0
1
Order By: Relevance
“…10,11 However, other studies have not reported significant changes in negative symptoms between glycine, d-serine or d-cycloserine and placebo, and thus were not able to replicate these findings. 12,13 A reason for these inconsistent results may be the considerable hetero geneity among patients with schizophrenia.…”
Section: J Psychiatry Neurosci 2017;42(4)mentioning
confidence: 99%
“…10,11 However, other studies have not reported significant changes in negative symptoms between glycine, d-serine or d-cycloserine and placebo, and thus were not able to replicate these findings. 12,13 A reason for these inconsistent results may be the considerable hetero geneity among patients with schizophrenia.…”
Section: J Psychiatry Neurosci 2017;42(4)mentioning
confidence: 99%
“…The use of D-serine to potentiate NMDA receptormediated neurotransmission has been particularly attractive because it is a more potent allosteric activator than glycine (Mothet et al, 2000), it is more permeable than glycine to the blood-brain barrier (Oldendorf, 1971) and it is not known to affect other neurotransmitter systems. There have been several small clinical studies ranging from 20 to 195 patients where D-serine has been tested in combination with other antipsychotics for the treatment of schizophrenia (Heresco-Levy et al, 2005;Kantrowitz et al, 2010;Lane et al, 2005Lane et al, , 2010Tsai et al, 1998Tsai et al, , 1999Weiser et al, 2012). Patients who have received D-serine have shown improvement in some clinical studies (Heresco-Levy et al, 2005;Kantrowitz et al, 2010;Tsai et al, 1998), whereas in others there was no effect (Lane et al, 2005(Lane et al, , 2010Tsai et al, 1999;Weiser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several small clinical studies ranging from 20 to 195 patients where D-serine has been tested in combination with other antipsychotics for the treatment of schizophrenia (Heresco-Levy et al, 2005;Kantrowitz et al, 2010;Lane et al, 2005Lane et al, , 2010Tsai et al, 1998Tsai et al, , 1999Weiser et al, 2012). Patients who have received D-serine have shown improvement in some clinical studies (Heresco-Levy et al, 2005;Kantrowitz et al, 2010;Tsai et al, 1998), whereas in others there was no effect (Lane et al, 2005(Lane et al, , 2010Tsai et al, 1999;Weiser et al, 2012). Only one study examined D-serine dose response (30-120 mg/kg/day) and the most improvement was seen at doses ⩾ 60 mg/kg/day (Kantrowitz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Zn serves as an endogenous neuromodulator of several important transmitters (19) and this role can be used for explaining its mechanism of action in the improvement of schizophrenia. There is growing the body of evidence implicating glutamatergic system in the pathophysiology of schizophrenia (4,17,18,38). Along with the studies reporting the efficacy of NMDA receptor allosteric agonists at the glycinB site in schizophrenia (4) some scientists have hypothesized the possible efficacy of NMDA antagonists in this disorder (4,39).…”
Section: Discussionmentioning
confidence: 99%